Changes in the structure of the phytoplankton community in a nile tilapia fishpond - Osti, João Alexandre Saviolo [UNESP]; Tucci, Andréa; Camargo, Antonio Fernando Monteiro [UNESP] (My University, 2018)
Aim: Our objectives were to recognize species that can serve as biological descriptors and evaluate the changes in the phytoplankton community throughout the grow-out period of the Nile tilapia (Oreochromis niloticus Linnaeus 1758) related to management practices and to limnological variables. Methods: Samples from the inflow water and the fishpond were collected for the analysis of limnological variables and the structure of the phytoplankton community. Results: In the fishpond, we registered a 1.5 times increase in nitrogen and total suspended solids and a 2 times increase in phosphorous compared to the inflow water. During the grow-out period (113 days), 134 taxa belonging to 10 taxonomic classes were registered. Chlorophyceae (60 taxa) and Cyanobacteria (26 taxa) showed the greatest diversity and abundance of species. The largest biovolumes were recorded in the fishpond. Nanoplanktonic species were the most abundant and represented 35% of the descriptor species in the phytoplankton community of the fishpond. Conclusions: The instability of the system associated with the control of the hydraulic retention time as a consequence of management practices, favored the presence of species with small cellular dimensions. The decrease in air and water temperature registered at the end of the grow-out period probably favored the increase and persistence of diatoms.
Mudanças na estrutura da comunidade fitoplanctônica em viveiro de tilápia-do-nilo
Keywords: Descriptor species; Ecology of fishponds; Microalgae; Nutrient cycle